Fahr's Syndrome With Hypoparathyroidism in a Patient With Schizophrenia and Iron Deficiency Anemia: A Case Report - Ali Haider; Ali Danish; Allahdad Khan; Atta Ur Rehman; Muhammad Haris Latif; Salman Abdul Basit; Aseel Kamal; Obaid Imtiyazul Haque (Clinical Case Reports)
ABSTRACT Fahr's syndrome is a rare neurological disorder that shows up as calcium deposits in the brain, affecting motor control and cognitive functions. In this case report, a 45‐year‐old woman with schizophrenia was diagnosed with Fahr's syndrome, which can be challenging to diagnose due to coexisting neurological comorbidity.